A method of estimating the velocity of moving targets for use in high-resolution wide-swath SAR imaging. Issue 4 (3rd April 2018) - Wang, Xiangyu; Wang, Robert; Li, Ning; Fan, Huaitao; Wang, Yuying
ABSTRACT: High-resolution wide-swath (HRWS) synthetic aperture radar (SAR) systems utilize multiple along-track channels to collect additional samples under relatively low pulse repetition frequency (PRF). This manuscript focuses on cross-track velocity estimation of a moving target in HRWS SAR, since this information is an important input parameter to HRWS non-uniform reconstruction and focusing of a moving target. However, velocity estimation in HRWS SAR would face the problems of the Doppler ambiguous image due to under-sampled data in the single channel. In this manuscript, the velocity of a moving target is modeled as phase offset vector. And then the problem of estimating velocity is transformed to find the optimal solution of the proposed cost function. The simulations are conducted to evaluate the performance and effectiveness under different along-track velocities, signal-to-noise ratios, and clutter models. The proposed method is also validated using airborne SAR data with four along-track channels.